2019
DOI: 10.1111/jcmm.14720
|View full text |Cite
|
Sign up to set email alerts
|

Histamine deficiency delays ischaemic skeletal muscle regeneration via inducing aberrant inflammatory responses and repressing myoblast proliferation

Abstract: Histidine decarboxylase (HDC) catalyses the formation of histamine from L‐histidine. Histamine is a biogenic amine involved in many physiological and pathological processes, but its role in the regeneration of skeletal muscles has not been thoroughly clarified. Here, using a murine model of hindlimb ischaemia, we show that histamine deficiency in Hdc knockout (Hdc−/−) mice significantly reduces blood perfusion and impairs muscle regeneration. Using Hdc‐EGFP transgenic mice, we demonstrate that HDC is expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…HDC deficiency led to the accumulation of CD11b þ Ly6G þ immature myeloid cells, 6 and inhibited CD8 þ T-cell proliferation. 7 The histamine signal also promotes the differentiation of macrophages 8,9 and monocyte-derived dendritic cells. 10 Furthermore, the H 2 -receptor-mediated signal was shown to be pivotal for the maintenance of myeloid-biased hematopoietic stem cells 11 and the differentiation of human monocyte-derived M1 macrophages, 12 suggesting a potential role of disrupted histamine signaling-mediated immunologic disorders in the development of hypertrophic gastropathy in HDC-deficient mice.…”
mentioning
confidence: 99%
“…HDC deficiency led to the accumulation of CD11b þ Ly6G þ immature myeloid cells, 6 and inhibited CD8 þ T-cell proliferation. 7 The histamine signal also promotes the differentiation of macrophages 8,9 and monocyte-derived dendritic cells. 10 Furthermore, the H 2 -receptor-mediated signal was shown to be pivotal for the maintenance of myeloid-biased hematopoietic stem cells 11 and the differentiation of human monocyte-derived M1 macrophages, 12 suggesting a potential role of disrupted histamine signaling-mediated immunologic disorders in the development of hypertrophic gastropathy in HDC-deficient mice.…”
mentioning
confidence: 99%
“…Histamine is an organic molecule based on the ammonia (NH 3 ) structure, which plays various biological roles such as in the regulation of immune responses ( 17 ), neurotransmission ( 18 ), and gastric acid secretion ( 19 ). In the innate immune system, histamine signaling is a primary factor in the allergic responses by mast cells, and further promotes the differentiation of macrophages ( 20 , 21 ), monocyte-derived dendritic cells (DCs) ( 22 ), hematopoietic stem cells ( 23 ), and human M1-type macrophages ( 24 ). Endogenous histamine is generated through the decarboxylation of histidine by histidine decarboxylase (HDC) ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…24 Abudupataer et al have reported that histamine acts on myoblast proliferation and muscle regeneration in histidine decarboxylase-knockout mice. 33 These findings suggest that Lanserine increases the contractile force of skeletal muscle via H1R. On the other hand, the L-anserine-induced increase in muscle contractility was not affected by the addition of H2R or H3R antagonists (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Gurel et al have reported that histamine improves muscle strength in mdx mice . Abudupataer et al have reported that histamine acts on myoblast proliferation and muscle regeneration in histidine decarboxylase-knockout mice . These findings suggest that l -anserine increases the contractile force of skeletal muscle via H1R.…”
Section: Discussionmentioning
confidence: 99%